Analisis Economic Value Added (EVA) dan Market Value Added (MVA) sebagai Alat Pengukur Kinerja Keuangan PT SA (Jurnal Manajemen dan Organisasi, 2016)
The company should demonstrate good financial performance to attract investors by financial performance based on value-added and market value. The objectives of this study at PT SA limited were: (1) To analyze the financial performance by Economic Value Added (EVA) method, (2) To analyze the financial performance by Market Value Added (MVA) method. The results showed the company was not able to add economic value to the company, which proved by EVA in 2008 was higher than in 2009. It is concluded that the company can not afford to pay obligations to investors as expected. However, different result showed by MVA, which indicates the company succes to managed the investor confidence over a given capital by increasing the value of capital invested. MVA showed results in 2008, the value of MVA was positive, and in 2009, the company's MVA achieved a significant increase in the amount of 379.42% from the previous year. The share price continued to increase making the MVA values continue to rise.